Virtual enterprise and e-business: a case study in a Brazilian aircraft company. (21st September 2006) - Amato Neto, Joao
The aim of this paper is to investigate the use of Virtual Organisation (VO) and Virtual Enterprise (VE) conceptions in the most important Brazilian aircraft company – Embraer, and to analyse the main impacts of these conceptions on its competitiveness power. The methodological framework is based on a unique case study supported by data collection techniques involving some strategic departments of the Brazilian aircraft company, especially Research and Development (R&D), engineering, Supply Chain Management (SCM) and Customer Relationship Management (CRM) areas. Moreover, this work intends to question some existing myths about the extension of the VE application and try to identify some technical and organisational obstacles and solutions concerning the implementation and development of the VO and VE concepts in this case.